1967
DOI: 10.1021/ac60256a019
|View full text |Cite
|
Sign up to set email alerts
|

Atomic fluorescence flame spectrometric detection of palladium, titanium, zirconium, chromium, and aluminum using a hot hollow cathode lamp

Abstract: was noticed. The demountable hot hollow cathode is a simple, practical, and intense excitation source for atomic fluorescence flame spectrometry and may prove useful in other flame spectrometric work. ACKNOWLEDGMENTWe are indebted to Camillo Massoni, U.S. Geological Survey, for construction of the hot hollow cathode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1968
1968
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 8 publications
(8 reference statements)
0
8
0
Order By: Relevance
“…They found that the intensities of the lines emitted during the pulse were several hundred times higher than with dc excitation, and that there was no significant increase in line width or self absorption. A demountable hollowcathode lamp giving intensities high enough for atomic fluorescence spectrometry was developed by Dinnin and Helz (180), and Dinnin (129) demonstrated that analytically useful fluorescence signals could be obtained with such lamps for palladium, titanium, zirconium, chromium, aluminum, manganese, cobalt, and iron, although no fluorescence was observed for 11 other elements tested.…”
Section: References Werementioning
confidence: 99%
“…They found that the intensities of the lines emitted during the pulse were several hundred times higher than with dc excitation, and that there was no significant increase in line width or self absorption. A demountable hollowcathode lamp giving intensities high enough for atomic fluorescence spectrometry was developed by Dinnin and Helz (180), and Dinnin (129) demonstrated that analytically useful fluorescence signals could be obtained with such lamps for palladium, titanium, zirconium, chromium, aluminum, manganese, cobalt, and iron, although no fluorescence was observed for 11 other elements tested.…”
Section: References Werementioning
confidence: 99%
“…The complete unit proves suitable for the detection of 14 metals in parts per billion concentrations. A demountable hot hollow cathode lamp suitable for obtaining the fluorescence response of 14 elements has been described by Dinnin (58); and Dagnall, Thompson, and West have given details for the production and operation of microwave-excited and electrodeless discharge tubes for use (55) in atomic fluorescence and atomic absorption spectroscopy. A simple atomic absorption photometer has been described (228) which proves to be quite satisfactory for the analysis of waters for the common metal impurities.…”
Section: Apparatusmentioning
confidence: 99%
“…Both Cd (155) and Zn (415) can be determined in the order of 0.1 ppb and several other elements also approach this sensitivity as methods for this technique improve. Dinnin and Helz (175) describe a demountable cathode lamp as an excitation source for atomic fluorescence and Dinnin gives a series of results with this source (174). Results with a xenon arc as a continuous source show less sensitivity than other sources (4-14)• Ellis and Demers show the use of a hydrogen-air flame in atomic fluorescence (199).…”
Section: Inorganicmentioning
confidence: 99%